History of paleobotany in Argentina during the 19th century: Scientists, explorers and the country on display - Ottone, E.G. (2011)
Plant fossil findings published in the nineteenth century by page, Grondona, Villegas, rhode, bove, Ave ́-lallemant, bodenbender and roth, references by Ameghino, Valentin, rickard, brackebusch, sarmiento and latzina, and these published in catalogues and memoirs of local and international exhibitions, together with plant fossil findings by Canard, Claraz, Hatcher, olascoaga and pietrobelli, that remained unpublished up to the twentieth century, are commented.